Analisis Sanksi Ekonomi Terhadap Rusia Atas Invasinya di Ukraina 2022 - Khisna Kamalia Zulfa; Arisanto, Puguh Toko; Khansa Rulif Mahadana (Department of International Relations, Brawijaya University, 2022)
Western countries as sender states have imposed economic sanctions on Russia for its invasion of Ukraine since February 2022. Sender states claimed that Russia had violated international law and human rights. The economic sanctions imposed on Russia ranged from freezing state and individual assets to terminating export-import activities to halt the invasion. With a qualitative method, this paper seeks to analyze the effectiveness of the economic sanctions imposed by sender states . The authors use the concept of economic sanction that some scholars argue that most of the economic sanctions are proven ineffective in changing behaviors of the target. In line with this postulate, the authors found that economic sanctions imposed by western countries and their allies on Russia are not effective. Until August 2022, economic sanctions imposed on Russia were unable to stop Russia's invasion of Ukraine. The authors argue that the ineffectiveness of the sanctions is influenced by at least three factors; dependence on Russian energy, Russia's resistance to economic sanctions and Putin's individual factors. Keywords: Economic Sanction, Russia Invasion, Sender, Target, Ineffective